Management Accounting Concepts for Inner Source Software Engineering - Hirsch, Julian; Riehle, Dirk (Lecture Notes in Business Information Processing, 2022)
Inner source software development is the use of open source development’s best practices inside a company. In inner source, developers collaborate on reusable software components across company-internal organizational silo boundaries for mutual benefit. As such, inner source goes against the grain of traditional management techniques. In this article, we present two conceptual models of management accounting for inner source. We derived these prototypes by performing a literature review and triangulating the results with interviews of industry practitioners. We demonstrate how the conceptual models can be used for monitoring and controlling inner source projects and to determine their future viability.
CRIS-Team Scopus Importer:2022-12-09
Keywords: Business intelligence; Inner source; Management accounting; Software engineering